A Novel Semi-Autonomous Control Framework for Retina Confocal Endomicroscopy Scanning - Li, Zhaoshuo; Shahbazi, Mahya; Patel, Niravkumar; Sullivan, Eimear O'; Zhang, Haojie; Vyas, Khushi; Chalasani, Preetham; Gehlbach, Peter L.; Iordachita, Iulian; Yang, Guang-Zhong; Taylor, Russell H. (Proceedings of the ... IEEE/RSJ International Conference on Intelligent Robots and Systems, 2019)
In this paper, a novel semi-autonomous control framework is presented for enabling probe-based confocal laser endomicroscopy (pCLE) scan of the retinal tissue. With pCLE, retinal layers such as nerve fiber layer (NFL) and retinal ganglion cell (RGC) can be scanned and characterized in real-time for an improved diagnosis and surgical outcome prediction. However, the limited field of view of the pCLE system and the micron-scale optimal focus distance of the probe, which are in the order of physiological hand tremor, act as barriers to successful manual scan of retinal tissue.Therefore, a novel sensorless framework is proposed for real-time semi-autonomous endomicroscopy scanning during retinal surgery. The framework consists of the Steady-Hand Eye Robot (SHER) integrated with a pCLE system, where the motion of the probe is controlled semi-autonomously. Through a hybrid motion control strategy, the system autonomously controls the confocal probe to optimize the sharpness and quality of the pCLE images, while providing the surgeon with the ability to scan the tissue in a tremor-free manner. Effectiveness of the proposed architecture is validated through experimental evaluations as well as a user study involving 9 participants. It is shown through statistical analyses that the proposed framework can reduce the work load experienced by the users in a statistically-significant manner, while also enhancing their performance in retaining pCLE images with optimized quality.